2021
DOI: 10.2174/1567201818666210202105531
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Inorganic Nanoparticle Complexes against CCL4 Induced Hepatotoxicity

Abstract: Background: Combination of different chemotherapy drugs and nanoparticles as a carrier have shown promising delivery system in cancer treatment. Doxorubicin is considered as a potent anticancer drug. However, it’s off target activities and possible side effects, make its use limited. Recently, in the field of nanomedicine, different nanoconjugates have been developed as a unique platform for the delivery of therapeutic drugs. Objective: The aim of present study was to evaluate the best possible combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For example, metal oxide NPs (for example. Ag, ZnO, TiO2) induce M1 inflammatory cytokines in a dose-dependent manner [128,129].In addition, Au NPs are more effective than Ag NPs related to particle size [130]. Moreover, NPs not only induce polarization of macrophages but also reprogram them [131] SPION, glycocalyx-mimicking [132] and carbosilane dendrimer [133] induced a shift of M2 macrophages to M1 phenotype and restored the activity of CD8 + T cells, resulting in an immunological memory effect.…”
Section: Targeted Specialty Apcs An Innate Immune-like Therapymentioning
confidence: 99%
“…For example, metal oxide NPs (for example. Ag, ZnO, TiO2) induce M1 inflammatory cytokines in a dose-dependent manner [128,129].In addition, Au NPs are more effective than Ag NPs related to particle size [130]. Moreover, NPs not only induce polarization of macrophages but also reprogram them [131] SPION, glycocalyx-mimicking [132] and carbosilane dendrimer [133] induced a shift of M2 macrophages to M1 phenotype and restored the activity of CD8 + T cells, resulting in an immunological memory effect.…”
Section: Targeted Specialty Apcs An Innate Immune-like Therapymentioning
confidence: 99%
“…Additionally, the protective effects of selenium nanoparticles were also observed in histopathological samples in preclinical models of hepatoxicity [ 26 ]. In another study by Tabbasam et al, the researchers investigated the protective effects of inorganic nanoparticle complexes against carbon tetrachloride-induced hepatotoxicity in preclinical mouse models [ 27 ]. In detail, these researchers generated three different types of nanoparticles (gold, silver, and zinc oxide) all loaded with doxorubicin.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, nanoparticle-assisted delivery of doxorubicin resulted in a reduced level of liver fibrosis. Moreover, they reported that silver nanoparticles loaded with doxorubicin outperformed the other types of nanoparticles by mediating the level of hepatic enzymes closest to the control group [ 27 ]. Overall, it was reported that drug-loaded silver nanoparticles demonstrated remarkable protective effects against carbon tetrachloride-induced hepatotoxicity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a plethora of inorganic nanomaterials have been investigated for possible use as nanocarriers for liver fibrosis therapy. Among these, Au, Ag or Pt nanoparticles (NPs), which exhibit good biocompatibility with negligible toxic side effects, have been exploited 24 , 25 . Interestingly, owing to the synergistic effect of two components, bimetallic nanoalloys tend to exhibit superior chemical properties and better catalytic performance than single-component NPs.…”
Section: Introductionmentioning
confidence: 99%